Studi Kasus Pemeriksaan Radiografi Kegawatdaruratan Abdomen Akut pada Kasus Ileus Obstruktif di RSI Sultan Agung Semarang - Hajratul Hikmah; Fisnandya Meita Astari; Asih Puji Utami (Universitas Muhammadiyah Manado, 2025)
The abdomen is a part of the body with the upper limit of the diaphragm and the lower limit of the pubic symphysis, inside there are three organ systems. One of the pathologies of the acute abdomen is obstructive ileus, which occurs when the contents of the lumen of the digestive tract cannot be passed to the anus due to obstruction. In acute abdominal radiographic examination in cases of obstructive ileus using AnteroPosterior (AP), Left Lateral Decubitus (LLD), and upright AP projections, the exposure waiting time is 5 or 10 to 20 minutes. At the RSI Sultan Agung Semarang Installation, AP and LLD projections are used, and the exposure waiting time is 5 minutes. The aim is to determine the procedure for examining the acute abdomen in cases of obstructive ileus, the Ap and LLD projections used and the exposure waiting time is 5 minutes. The type of descriptive qualitative research with a case study approach. The subjects of the study were 3 radiographers, 1 radiology specialist, 1 referring doctor. The objects of the study were patients undergoing acute abdominal examination. Data collection methods were observation, interviews, and documentation. The data were analyzed by means of transcription, reduction, categorization tables, open coding, and conclusions were drawn. Results acute abdominal examination in cases of ileus has no special preparation, only removing metal objects that can interfere with the radiograph results, the projections used are AP and LLD. LLD projection can clarify the visualization of the Air Fluid Level level, the use of the LLD position can help establish a more accurate diagnosis of obstructive ileus. The exposure waiting time is 5 minutes, with that time it has shown free air in the abdominal cavity.